Self-assembly of colloidal MOFs derived yolk-shelled microcages as flexible air cathode for rechargeable Zn-air batteries. (November 2021) - Li, Zhaoqiang; Yang, Jingyi; Ge, Xiaoli; Deng, Ya-Ping; Jiang, Gaopeng; Li, Haibo; Sun, Guiru; Liu, Wenwen; Zheng, Yun; Dou, Haozhen; Jiao, Hailiang; Zhu, Jianbing; et al.
Abstract: It is still an urgent but challenging task to rational design metal organic frameworks (MOFs)-derived architectures with decent oxygen bifunctionality and durability on substrates for the development of flexible Zn-air batteries (ZABs). Herein, unique yolk-shelled microcages with Co-Nx -C decorations (Co-Nx -YSC) are designed and fabricated on carbon cloth (CC) through a proposed self-assembly strategy. Prior to assembly on carbon-based substrates pretreated with negative charge, the cationic modified colloidal MOFs with controllable morphology and composition were synthesized. After calcination of the obtained ZIF-67/CC under 600 °C, the flexible electrode Co-Nx -YSC-600/CC is obtained, which exhibits excellent oxygen bifunctionality, good cycling stability (400 cycles at 10 mA cm −2 ) and outstanding flexibility when directly employed as air electrode in flexible ZABs. Such yolk-shelled architecture not only optimizes the reactants availability towards active sites, but also provides capacious spaces for oxygen reactions and the corresponding mass transportation. Besides, the interconnected carbon nanotube frameworks can further ensure fast charge transfer and serve as the robust host for Co-Nx -C active sites. With these structural merits, Co-Nx -YSC-600/CC showcases its promises as air electrode for flexible ZABs. Graphical Abstract: ga1 Highlights: Self-assembly of colloidal MOFs crystals on carbon-based substrates was achieved. Yolk-shelled CNT hollow microcages on carbon cloth (CC) were obtained. The microcages act as bifunctional oxygen electrocatalysts in flexible Zn-air batteries. The fabricated Zn-air battery exhibit a long cycle life of more than 400 cycles.